WAYS TO OPTIMIZE THE CASH RESOURCES MANAGEMENT AT THE ENTERPRISE - Akhmetova Aigul; Aimagambetova Aida; Oralbayeva Aizhan; Bisembayeva Gulnur (Scientific Journal of Pedagogy and Economics, 2021)
To maintain the financial stability of the enterprise at a stable high level and increase it, it is necessary to increase the accumulation speed of its own sources. To do this, it is necessary to find reserves, as well as provide material working capital from own sources. In addition, it is necessary to find an optimal balance of financial resources, the free flow of funds of the enterprise can ensure a continuous process of production and sale of products through their effective use. In the conditions of financial stability of the enterprise, we would like to note that effective cash flow management is the most important developed system.The cash flow management system of an enterprise is a system of tasks and methods for the formation, use and distribution of funds, as well as the development and implementation of management decisions related to the implementation of the company’s turnover.The main objectives of cash management are not only to increase cash flows, but also to ensure the financial balance and stability of the enterprise in the course of its operation. This is done by balancing the amount of received and spent money and by coordinating it. It provides the mechanisms and indicators of financial stability of the enterprise, as well as the factors affecting cash to ensure the financial sustainability of the enterprise, methods and mechanisms of management of cash flows in terms of financial stability. Also, the effectiveness of cash management plays an important role in assessing the company’s financial stability indicators. In order to achieve financial stability of the company, the factors affecting cash were considered. Any organization should choose methods for increasing, balancing, and synchronizing cash flows appropriate to its condition. The analysis reveals shortcomings in the company’s activities and measures aimed at improving the efficiency of its work.